2022
DOI: 10.3390/insects13030266
|View full text |Cite
|
Sign up to set email alerts
|

Agronomic Factors Influencing Fall Armyworm (Spodoptera frugiperda) Infestation and Damage and Its Co-Occurrence with Stemborers in Maize Cropping Systems in Kenya

Abstract: Fall armyworm (FAW), Spodoptera frugiperda J.E Smith, (Lepidoptera: Noctuidae) is a serious invasive pest of maize that has been established in Kenya since 2016. Little is known about its co-occurrence with resident stemborers, relative infestation and damage and how agronomic factors influence its infestation and damage in maize cropping systems across different agro-ecological zones. This study assessed FAW co-occurrence with resident stemborers, relative infestation and damage across three agro-ecological z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 51 publications
1
34
0
Order By: Relevance
“…In addition, pesticides with greater toxicity against early-instar larvae or with strong ovicidal activity should be used at the seedling/jointing/flare opening/spinning stages. Furthermore, together with the previous findings, the degree of damage to maize and the population density of S. frugiperda were found to relate to the growth period, variety, and location of maize, the age of the pest, the season, field temperature, light, region, plant species in the nearby habitat, as well as to local pest management measures [ 13 , 46 , 48 ].…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…In addition, pesticides with greater toxicity against early-instar larvae or with strong ovicidal activity should be used at the seedling/jointing/flare opening/spinning stages. Furthermore, together with the previous findings, the degree of damage to maize and the population density of S. frugiperda were found to relate to the growth period, variety, and location of maize, the age of the pest, the season, field temperature, light, region, plant species in the nearby habitat, as well as to local pest management measures [ 13 , 46 , 48 ].…”
Section: Discussionsupporting
confidence: 52%
“…This showed that the pest favors the heart leaves and female ears, which are young parts of maize plants that are critical for the growth as well as the development of maize; this may be one of the reasons why the pest is significantly harmful. Previous studies conducted by Tang et al [ 47 ] and Mutyambai et al [ 48 ] found that S. frugiperda larvae had a significant preference for the tender parts of plants. In addition, the composition and structure of larvae were different at different growth stages of maize.…”
Section: Discussionmentioning
confidence: 99%
“…Our data can also add AAW to the list of other lepidopteran larvae sharing a eld with FAW 25,29,34,41−43 including beet armyworm (Spodoptera exigua) 43 and taro caterpillar (Spodoptera litura) 34 . The current literature about the co-occurrence of FAW and other species mainly covers the Indomalayan realm, China 34,43,54−56 and India 57 and limited data from the other biogeographic realms such as the Americas 42 , Cuba 27 and Africa 29,41,58 . Our study could have broader relevance to Tanzania and other areas of Africa since the AAW 2022 outbreak is reported to have affected Zimbabwe, Kenya, and Uganda 13 .…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of cannibalistic and predatory behaviour of FAW larvae may intensify inter-speci c competition and predation between the two armyworm species 17,18,33-38,25−32 as FAW often attack other species 33 , including predators such as the stinkbug (Supputius cincticeps) 39 and hover y (Eupeodes corollae) 40 . FAW competition studies have so far tended to focus on stemborers like the maize stalk borer (Busseola fusca), African pink stemborer (Sesamia calamistis), the pink stemborer (Sesamia inferens) and the spotted stalk borer (Chilo partellus) 29,41 , as well as some other Lepidoptera, such as the corn earworm (Helicoverpa zea) 25 and cotton bollworm (Helicoverpa armigera) 42 . These studies generally conclude that there is strong competition between FAW and other Lepidoptera larvae except H. virescens, H. zea and stemborers.…”
Section: Introductionmentioning
confidence: 99%
“…Based on this incident, many attribute the rapid adaptability to the advantage for these insect pests to invade quickly into various areas [9]. The potential spread of FAW can be influenced by climate, expansion of host plants, to agricultural commodity trading activities [10,11].…”
Section: Introductionmentioning
confidence: 99%